Hubungan Karakteristik Biologis Gambut dengan Penyakit Busuk Batang yang Disebabkan Ganoderma pada Kelapa Sawit - Supriyanto Supriyanto; Purwanto Purwanto; S H Poromarto; Supyani Supyani (Fakultas Pertanian Universitas Tanjungpura, 2021)
The relationship of biological properties of peat with oil palm basal stem rot (BSR) caused by Ganoderma. Indonesia as the largest palm oil producer in the world, has the large percentage of oil palm on peatland. The serious problems of cultivating oil palm on peatland is the presence of BSR disease caused by Ganoderma. There are no effective methods to control the spread of this disease. Biological control is an environmentally friendly alternative method focus, but on peatland, the development of this method is constrained by lack of information about the effect of biological environmental factors. This study aims to determine the effect of the biological propertiess of peat on the intensity of Ganoderma attacks on oil palm. The relationship between the intensity of Ganoderma attacks and biological properties of peat was carried out by correlation test. The correlation analysis showed that the biological properties of peat has not correlated with the Ganoderma attacks, except Summed Dominant Ratio of vegetation which tends to positively correlate to the number of Ganoderma antagonists. These results indicate that peatland vegetation management by maintaining the diversity of vegetation around oil palm can help reduce Ganoderma attacks.